Law and Application of Pancasila Principles in Interfaith Marriages in Indonesia - Irsan Rahman; Darmawati. R; Rica Regina Novianty; Erni; Basrawi (Inovasi Pratama Internasional. Ltd, 2024)
The implementation of the life of the nation and state is inextricably tied to the divine values encapsulated in Pancasila and the Constitution. However, the current reality of Indonesia's diverse nation poses a challenge to these divine values. The absence of barriers between individuals, as exemplified by their interactions and the formation of families through marriage, has resulted in the dissolution of ethnic, cultural, and religious distinctions. Consequently, some couples entering into marriage no longer consider their ethnic and cultural background as a determining factor in their relationship.The purpose of this paper is twofold: first, it aims to analyse the views of Pancasila and the 1945 Constitution of the Republic of Indonesia on the phenomenon of interfaith marriages in Indonesia; second, it seeks to provide confirmation of the actual legal status of these marriages. In order to achieve this, this paper employs a normative legal research methodology, utilising both a statutory and conceptual approach in its investigation. From a conceptual standpoint, marriage encompasses not only its legal and private aspects, but also its religious aspects. Therefore, the state relinquishes its authority to determine the legitimacy of marriage to religious law, which, by its nature, discourages interfaith marriages. This paper concludes that Pancasila and the 1945 Constitution do not acknowledge the existence of interfaith marriages, as they are deemed incompatible with divine values. Accordingly, the judiciary should refrain from recognizing interfaith unions. To resolve legal disputes surrounding these unions, the Population Administration Act should be amended to repeal Article 35, Paragraph 1.